APLIKASI VAKSIN Streptococcus agalactiae UNTUK PENCEGAHAN PENYAKIT STREPTOCOCCOSIS PADA BUDIDAYA IKAN NILA (Oreochromis niloticus) [Application of Streptococcus agalactiae vaccine to prevent streptococcosis on tilapia culture, Oreochromis niloticus] - Taukhid, Taukhid; Lusiastuti, Angela Mariana; Sumiati, Tuti (BERITA BIOLOGI, 2014)
The research with the aim to know the effectivity (yield gap) of the application of Streptococcus agalactiae vaccine (pure whole cell) in prevention of streptococcosis on tilapia (Oreochromis niloticus) culture has been carried out. The isolate of S.agalactiae â N14G was used as a master seed on vaccine production. Priming vaccination was administered by immersion method, and booster vaccination was taken th place two months latter by oral method. Challenge test at the lethal dose (LD50) against active bacteria was done at 14 days post booster vaccination, and observation was taken place for 14 days post artificial infection. The results of the research showed that the highest survival rate and relative percent survival (RPS) was found in group treated with Streptovac vaccine (S. agalactiae and A. hydrophila combination) (65.58% and 35.36%) followed by S. agalactiae vaccine (52.08% and 10.01%). The lowest survival rate was found in control group (46.75%). The result of confirmation effectivity of the vaccines by challenge test in the laboratory showed that the highest survival rate and relative percent survival (RPS) was found in S. agalactiae vaccine (50.00% dan 37.50%) followed by Streptovac vaccine (40.00% and 25.00%), and the lowest survival rate was found in control group (20.00%). Vaccination is better than the non vaccinated.